2016
DOI: 10.18632/oncotarget.8604
|View full text |Cite
|
Sign up to set email alerts
|

The pathological role of advanced glycation end products-downregulated heat shock protein 60 in islet β-cell hypertrophy and dysfunction

Abstract: Heat shock protein 60 (HSP60) is a mitochondrial chaperone. Advanced glycation end products (AGEs) have been shown to interfere with the β-cell function. We hypothesized that AGEs induced β-cell hypertrophy and dysfunction through a HSP60 dysregulation pathway during the stage of islet/β-cell hypertrophy of type-2-diabetes. We investigated the role of HSP60 in AGEs-induced β-cell hypertrophy and dysfunction using the models of diabetic mice and cultured β-cells. Hypertrophy, increased levels of p27Kip1, AGEs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Increasing evidence reveals that high dose of therapeutic glucocorticoid disturbs mitochondrial machinery provoking cell damage or tissue deterioration, like skeletal muscle wasting 28 , necroptosis of acute lymphoblastic leukemic cells 29 , and fat overproduction of adipose tissue 30 . Loss of HSP60 function also perturbs extracellular matrix metabolism and amplifies apoptotic programs 31 , 32 . This study showed that HSP60 maintained autophagic influx beneficial for fending off glucocorticoid-induced apoptosis and mineralized matrix underproduction, indicating that glucocorticoid stress cutoff a fine-tuned organelle crosstalk between autophagosome and mitochondria aggravating osteoblast dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence reveals that high dose of therapeutic glucocorticoid disturbs mitochondrial machinery provoking cell damage or tissue deterioration, like skeletal muscle wasting 28 , necroptosis of acute lymphoblastic leukemic cells 29 , and fat overproduction of adipose tissue 30 . Loss of HSP60 function also perturbs extracellular matrix metabolism and amplifies apoptotic programs 31 , 32 . This study showed that HSP60 maintained autophagic influx beneficial for fending off glucocorticoid-induced apoptosis and mineralized matrix underproduction, indicating that glucocorticoid stress cutoff a fine-tuned organelle crosstalk between autophagosome and mitochondria aggravating osteoblast dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the proteomics data indicated a significant downregulation of many proteins involved in insulin granules exocytosis (Figure 3B; Table S1). Thus, our data provide a molecular explanation for the insulin secretion failure observed in islets from 10-to 13-week-old db/db mice (Do et al, 2014;Guan et al, 2016;Kim et al, 2015;Kondo et al, 2012). The lower [ATP]/[ADP] concentration ratio in db/db islets should promote AMPK activation, which is likely to be inhibited (Figure 2A).…”
Section: Pdx1 Suppression Downregulates Glut2 and Inhibitsmentioning
confidence: 75%
“…Mice heterozygous for the Hspd1 gene, encoding HSP60, (Hsp60 +/− mice) can serve as a genetic model for diabetes-related mitochondrial dysfunction, as db/db mice exhibit an approximately 50% reduction in HSP60 ([ 9 , 22 , 23 ], Attie Lab diabetes database http://diabetes.wisc.edu/ ). This model allows for an answer to the question of whether a mild generalized impairment in mitochondrial function due to decreased chaperone activity, as seen in diabetes, affects insulin action and obesity development.…”
Section: Introductionmentioning
confidence: 99%